2017
DOI: 10.1108/jcm-07-2015-1505
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature cues on charitable donation

Abstract: Purpose This paper aims to investigate how the perception of physical coldness (vs warmth) influences consumers to make charitable donations. Design/methodology/approach Three experiments were conducted involving charitable donation scenarios. Findings Studies demonstrate that cold (vs warm) temperature cues result in greater intentions to donate to charities. Specifically, cold (vs warmth) cues activate the need for social connection which, in turn, motivate consumers to donate more money to charities. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Based on the insights from the effect of physical warmth on social perception in grounded cognition theory, our study extends the current knowledge to retail contexts by providing warmth experience through a store atmosphere. With the use of design elements such as interior color and materials that are known to provide warmth perception (e.g., Fenko et al, ), we found the visually warm (vs. cold) store atmosphere was also associated to warm (vs. cold) temperature consistent with the finding by Rai et al (). We further investigated the effect of visually warm (vs. cold) store atmosphere on consumers' perception based on the metaphoric link between warmth experience and perceptions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Based on the insights from the effect of physical warmth on social perception in grounded cognition theory, our study extends the current knowledge to retail contexts by providing warmth experience through a store atmosphere. With the use of design elements such as interior color and materials that are known to provide warmth perception (e.g., Fenko et al, ), we found the visually warm (vs. cold) store atmosphere was also associated to warm (vs. cold) temperature consistent with the finding by Rai et al (). We further investigated the effect of visually warm (vs. cold) store atmosphere on consumers' perception based on the metaphoric link between warmth experience and perceptions.…”
Section: Discussionsupporting
confidence: 88%
“…Second, this study approached the warmth experience holistically (i.e., a store atmosphere). Although several atmospheric researchers have demonstrated the significant role of an ambient environment in changing consumer behaviors (Dijksterhuis, Smith, van Baaren, & Wigboldus, ), recent findings on the effect of visually perceived warmth merely considered color (Choi et al, ) or pictures that depict warmth (Rai et al, ). Extending the range of stimulation to a store environment, we find a visual warm atmosphere to be an ambience that influences consumers' evaluation of the store, as well as the products—even when the merchandise and its assortment are identical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have documented that perceived warmth is associated with interpersonal intimacy; that is, perceived warmth creates feelings of interpersonal closeness [ 73 ], and promotes interpersonal trust, cooperation, and friendship [ 74 ]. Specifically, warm colors are more evocative of warmth than cool colors [ 66 ] and provide consumers with a sense that their surroundings are more socially dense [ 75 ]. In this manner, a warm-toned interface of a medical crowdfunding website will bring warm psychological perceptions and positive attitudes to donors, making them feel less distant from the medical crowdfunding platform and other help-seekers, and thus more likely to evoke their emotional trust toward the platform and project.…”
Section: Introductionmentioning
confidence: 99%
“…When there is no uncertain situation, consumers are reluctant to alter their intentions easily towards brands because habit is more grounded than consumer intentions that impelled by fear (Young et al, 2010). Natural disasters have a deep impact on marketers because it effects on consumer shopping behavior (Rai et al, 2017).…”
Section: Discussionmentioning
confidence: 99%